Numerical simulation of the response of a reinforced wall to a high speed train passage. (1st February 2017) - Corfdir, A.; Bourgeois, E.; Payeur, J.‐B.
Summary: The dynamic response of a mechanically stabilized earth wall to the passing of a high‐speed train is modelled using the finite element method. A three‐dimensional analysis is carried out, using a specific framework that allows performing the analysis with a moderate computational effort. In the first place, a so‐called multiphase approach is used to take into account the reinforcing strips. The moving load is taken into account by performing the calculation in a mobile referential using the properties of symmetry of the train cars and a simplifying assumption of periodicity for the whole train. We also assume a steady state. A partial validation of the approach is obtained by means of a comparison with an analytical solution. The quick increase in displacements induced by the train passing when the speed comes close to the celerity of Rayleigh waves clearly appears in the results. The vertical displacements, vertical stresses in the backfill, tensile forces in the strips and the influence of the stiffness of the soil are discussed. Copyright © 2017 John Wiley & Sons, Ltd.